Penerapan Restorative Justice Terhadap Anak yang Menjadi Pelaku Tindak Pidana Melalui Diversi - Ririn Kurniasi (LPPM Universitas Ekasakti Padang, 2024)
The growth and development of children are influenced by many factors that lead children to become perpetrators of criminal acts and ultimately engage in criminal activities. In the process of resolving such cases as a form of deterrence, it is essential to remember to safeguard their mental well-being. According to Law No. 11 of 2012 on the juvenile justice system, the handling of such cases must apply restorative justice, which provides protection and upholds the inherent rights of the child. In this study, the author will discuss the implementation of restorative justice for children that involved in criminal activities through diversion and how to achieve the goals of diversion as outlined in Law No. 11/2012. The method used in this research is normative legal research. The study employs a legislative approach, with a specific examination of Law No. 11 of 2012 and other relevant legal regulations, supported by data that underpins the research. Data collection and analysis techniques involve primary data (journals and relevant research findings) and, secondary data (books and other references). Diversions manifest restorative justice in protecting children facing legal issues, allowing juvenile justice proceedings to occur outside the formal criminal justice process, as is typical for adults. Efforts to resolve juvenile criminal acts through diversion are carried out to the fullest extent possible. Article 13 of the Child Criminal Justice System Law (SPPA) emphasizes that if no agreement is reached in the diversion process between the victim and the criminal offender, or if the agreed-upon terms are not followed, the case will proceed to the juvenile justice process, following the formalities outlined in KUHAP. Diversions are not allowed for children who engage in repeated criminal acts. Therefore, further improvement in the guidance of child offenders under the subsequent legal regulations is necessary.